PENGEMBANGAN APLIKASI PELAPORAN KERUSAKAN BERBASIS ANDROID UNTUK PT KAYU MULTIGUNA INDONESIA DENGAN METODE RAD: Implementasi Metode RAD dalam Membangun Solusi Pelaporan Kerusakan - Majid, Ardian; dwi bhakti, henny (Program Studi Teknik Informatika FTI UNIBBA, 2023)
This research aims to address the issues of ineffective damage reporting at PT Kayu Multiguna Indonesia. These issues include delayed reporting and equipment failures that are not promptly resolved. The objective of this research is to develop an Android-based application using the Rapid Application Development (RAD) methodology to facilitate and expedite damage reporting while enabling better monitoring. The development process involves requirement analysis, visual user interface design, application development, as well as testing and continuous improvement. The result is an Android damage reporting application that allows employees to quickly report damages, reduce incident response times, and track repair statuses through the application. This application is expected to enhance the operational efficiency of PT Kayu Multiguna Indonesia by integrating Android technology and RAD methodology. The discussion covers the advantages and disadvantages of the application, as well as potential future improvements and developments. In conclusion, the Android-based damage reporting application developed with the RAD methodology successfully addresses the issues of inefficiency in reporting at PT Kayu Multiguna Indonesia. Suggestions for further development include enhancing the application's functionality, such as reporting with images or maps, and considering integration with the company's asset management system. This application is expected to assist PT Kayu Multiguna Indonesia in improving operational efficiency, accountability, and productivity in handling damages.